2015
DOI: 10.1183/09031936.00018215
|View full text |Cite
|
Sign up to set email alerts
|

Chymase: a multifunctional player in pulmonary hypertension associated with lung fibrosis

Abstract: Limited literature sources implicate mast-cell mediator chymase in the pathologies of pulmonary hypertension and pulmonary fibrosis. However, there is no evidence on the contribution of chymase to the development of pulmonary hypertension associated with lung fibrosis, which is an important medical condition linked with increased mortality of patients who already suffer from a life-threatening interstitial lung disease.The aim of this study was to investigate the role of chymase in this particular pulmonary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 48 publications
(86 reference statements)
2
38
0
Order By: Relevance
“…Paraffin-embedded human lung tissues were subjected to immunohistochemistry as previously described (Kosanovic et al, 2015) using polyclonal anti-FGF10 (Antibodies-online, ABIN360398, 1:30), monoclonal anti-ACTA2 (Sigma-Aldrich, 1:900) and polyclonal anti-vWF antibodies (Dako, 1:900). Masson's trichrome and hematoxylin/eosin stainings were performed according to standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded human lung tissues were subjected to immunohistochemistry as previously described (Kosanovic et al, 2015) using polyclonal anti-FGF10 (Antibodies-online, ABIN360398, 1:30), monoclonal anti-ACTA2 (Sigma-Aldrich, 1:900) and polyclonal anti-vWF antibodies (Dako, 1:900). Masson's trichrome and hematoxylin/eosin stainings were performed according to standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded human lung tissues were subjected to immunohistochemistry as previously described (Kosanovic et al, 2015) using polyclonal anti-FGF10 (Antibodiesonline, ABIN360398, 1:30), monoclonal anti-ACTA2 (Sigma-Aldrich, 1:900) and polyclonal anti-vWF antibodies (Dako, 1:900). Masson's trichrome and hematoxylin/eosin stainings were performed according to standard procedures.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Based on the hypothesis that chymase contributes to the development of fibrotic lesions, investigators have sought to interfere with fibrosis by administrating various chymase inhibitors. Indeed, the chymase inhibitors SUN‐C8077, BCEAB and NK3201 reduced bleomycin‐induced lung fibrosis in separate studies . Mechanistically, it was shown that chymase inhibition led to a decrease in the content of TGFβ and MMP2 in the lungs, and it was demonstrated that chymase inhibition prevented effects of endothelin‐1.…”
Section: Targeting Mast Cell Function In Fibrosismentioning
confidence: 99%
“…Indeed, the chymase inhibitors SUN-C8077, BCEAB and NK3201 reduced bleomycininduced lung fibrosis in separate studies. [227][228][229] Mechanistically, it was shown that chymase inhibition led to a decrease in the content of TGFβ and MMP2 in the lungs, and it was demonstrated that chymase inhibition prevented effects of endothelin-1. The latter observation is thus in agreement with a previous study where chymase was shown to be pivotal for the conversion of Big-endothelin-1 to endothelin-1.…”
Section: Inhibitors Of Protease Activitymentioning
confidence: 99%